Evaluating Best Practices for Video Tutorials: A Case Study. Issue 1 (2nd January 2017) - Weeks, Thomas; Putnam Davis, Jennifer
ABSTRACT: This article will explore one library's experience creating best practices for the creation of video tutorials. First, a literature review establishes the best practices other creators have used. Then, the authors apply these best practices to the creation of their first video tutorial. Finally, they evaluate the usefulness of each practice in context. This study is helpful for all those starting to make video tutorials or reinvigorate their tutorial creation.